2020
DOI: 10.1038/s41467-020-15578-1
|View full text |Cite
|
Sign up to set email alerts
|

FBXO22 degrades nuclear PTEN to promote tumorigenesis

Abstract: Nuclear localization of PTEN is essential for its tumor suppressive role, and loss of nuclear PTEN is more prominent than cytoplasmic PTEN in many kinds of cancers. However, nuclear PTEN-specific regulatory mechanisms were rarely reported. Based on the finding that nuclear PTEN is more unstable than cytoplasmic PTEN, here we identify that F-box only protein 22 (FBXO22) induces ubiquitylation of nuclear but not cytoplasmic PTEN at lysine 221, which is responsible for the degradation of nuclear PTEN. FBXO22 play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…Recently, FBXO22 was identified to mediate the Bach1 degradation and inhibit migration in lung cancer cells 47 . More recently, in agreement with the oncogenic role of FBXO22, phosphatase and tensin homolog on chromosome 10 (PTEN), a bona fide tumor suppressor, is validated as a direct substrate of FBXO22 48 . FBXO22 ubiquitinates and degrades nuclear PTEN via proteasome-mediated degradation in colorectal cancer, leading to tumor development 48 (Table 1 and Fig.…”
Section: Downstream Targets Of Fbxo22mentioning
confidence: 69%
See 1 more Smart Citation
“…Recently, FBXO22 was identified to mediate the Bach1 degradation and inhibit migration in lung cancer cells 47 . More recently, in agreement with the oncogenic role of FBXO22, phosphatase and tensin homolog on chromosome 10 (PTEN), a bona fide tumor suppressor, is validated as a direct substrate of FBXO22 48 . FBXO22 ubiquitinates and degrades nuclear PTEN via proteasome-mediated degradation in colorectal cancer, leading to tumor development 48 (Table 1 and Fig.…”
Section: Downstream Targets Of Fbxo22mentioning
confidence: 69%
“… Substrates Cell lines Functions Refs KDM4A HeLa, 293T, 293T-Rex Regulation of cell cycle, involves in development, differentiation, cancer 32 KDM4B MCF7, T47D Tomaxifen resistance 33 Methylated p53 HeLa, U2OS, MCF7, 293T, HCA2, MEFs, HCT116, RPE-1 Regulating senescence 34 p21 HL-7702, HepG2, Huh7, Hep3B, Bel-7402, HLF, LM3, 293T Promotes proliferation and tumor growth 35 KLF4 HepG2, Huh7, Hep3B Promotes proliferation and invasion 38 LKB1 H322, H446, H460, H661, H1299, BT549 Promotes cell growth 43 CD147 293T, A549, SMMC-7721, Huh-7 Inhibits cisplatin resistance 45 Bach1 A549, H2009, 293T, KP, KPK. Inhibits migration and metastasis 47 PTEN 293T, HeLa, SW620, SW480, LS174T Promotes tumor growth 48 Snail MDA-MB-231, Hs578T, MCF-7, ZR-75-1, T47D Inhibits migration, invasion, and metastasis; promotes proliferation 39 HDM2 HeLa, MDA-MB-231, BT-549, 4T1 Inhibits invasion and metastasis 42 …”
Section: Downstream Targets Of Fbxo22mentioning
confidence: 99%
“…The mechanism of action of FBXO5 was related to poor prognosis in BC, which was worthy to make a profound study in the future. Overexpression of FBXO22 has been reported to promote nuclear tumor suppressive factor PTEN downregulation to play a tumor-promoting role in colorectal cancer [49]. However, Yoshikazu et al have showed that low levels of FBXO22 in HER2-negative BC predict a poorer outcome with high hazard ratios, independently of other markers such as Ki-67 and lymphenode status [50].…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the centromere is a result of RAD51 expression by PTEN modulation (Figure 2). Given that RAD51 is a key component of the double-strand breaks (DSB) homologous recombination (HR) DNA repair systems, PTEN is currently viewed as a DNA-damage response regulator [32,33]. Importantly, PTEN loss may lead to DSB also through increased Akt-mediated cytoplasmic sequestration of the checkpoint kinase 1 (CHK1), resulting in altered G2/S arrest in response to DNA damage [34].…”
Section: Nuclear Pten and Modulation Of The Dna Damage Responsementioning
confidence: 99%